Die Effekte der Zielorientierung auf den Berufserfolg: Erste empirische Befunde - Carlotta Böge; Jens K. Perret; Janine Netzel (Books on Demand (BoD), 2021)
– Regarding their Goal orientation people can be divided into those that strife to enhance their skills (learning goal orientation / LGO) and those that aim to demonstrate their advanced skills (performance-approach goal orientation / PApGO) or hide their inferior skills (performance-avoidance goal orientation / PAvGO). The study analyzes the relation between the two dimensions of goal orientation and the career success based on a sample of 260 participants of age 50+ that are currently employed or have been so in the past. For the LGO the expected positive relation with the career success can only be established for the self-assessed career success. Opposed to theoretical arguments the negative relation between PApGO and career success cannot be established. For the PAvGO the expected negative relation could, however, be established. Additionally, it has been shown that an effect of conscientiousness on the relation between LGO and career success is likely.
Keywords: 330